2016
DOI: 10.1136/annrheumdis-2016-209253
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of reference intervals for osteoarthritis-related soluble biomarkers: the FNIH/OARSI OA Biomarkers Consortium

Abstract: To our knowledge, this represents the best and most stringent control group ever assayed for OA-related biomarkers. These well-phenotyped controls, representing a similar age demographic to that of the OA Initiative-FNIH main study sample, provide a context for interpretation of OA subject biomarker data. The freely available data set also provides a reference for future human studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 11 publications
1
40
1
2
Order By: Relevance
“…Our analyses were performed both with and without the inclusion of covariates, including age, sex, BMI, and K/L grade. It has been demonstrated that these demographic features and K/L grade may affect bone biochemical markers levels . Moreover, they were often independently associated with the imaging markers in our study.…”
Section: Discussionsupporting
confidence: 53%
“…Our analyses were performed both with and without the inclusion of covariates, including age, sex, BMI, and K/L grade. It has been demonstrated that these demographic features and K/L grade may affect bone biochemical markers levels . Moreover, they were often independently associated with the imaging markers in our study.…”
Section: Discussionsupporting
confidence: 53%
“…commercially available biomarkers were associated with age: sHA (rho ¼ 0.19), PIIANP (rho ¼ 0.27) and C1,2C (rho ¼ 0.20). Likewise gender differences were seen for uCTX-II, MMP-3, uCol2-1 NO 2 and sHA 45 . Cartilage damage and concentrations of sCOMP, sCTX-II, sMMP-3, sPIIINP, and sHA were determined in 79 patients who underwent knee arthroscopy or total knee replacement in a study by Jiao and colleagues 47 .…”
Section: Clinical Validation Of Existing Oa Biomarkersmentioning
confidence: 76%
“…During the past year, OARSI has published a set of recommendations for the use of soluble biomarkers in clinical trials. The OARSI-endorsed publications summarize the key steps necessary for the qualification of a biomarker as a drug development tool and the various contexts for which OA biomarkers may be used 45,46 . In an effort to qualify more biomarkers as drug development tools, the Foundation for the National Institutes of Health/Osteoarthritis Initiative (FNIH/OAI) biomarkers consortium ef released the results of their soluble (urinary, abbreviated with a prefix u and serum, abbreviated with a prefix s) biomarker analysis 45,46 .…”
Section: Clinical Validation Of Existing Oa Biomarkersmentioning
confidence: 99%
See 2 more Smart Citations